Model Diskoveri Inkuiri dan Penugasan Untuk Peningkatan Hasil Belajar dan Keuletan Siswa Pada Pelajaran Kewirausahaan - Suwarti Suwarti (Jurnal Dewantara, 2019)
Student achievement in entrepreneurship in basic competency (KD) shows the attitude of never giving up and being tenacious is still low. Half of the students get an average learning achievement under 50. This Classroom Action Research was conducted at SMK Negeri 3 Metro with a total of 34 students. Researchers can conclude that achievement, student tenacity in entrepreneurship and Entrepreneurship learning process, students of SMK Negeri 3 Metro in KD Demonstrating unyielding and tenacious attitude can be increased through learning using inquiry models guided by questions and answers, discussion and assignments. The average learning achievement in the pre-cycle 4.38 increased to 6.38 in the first cycle, then increased to 7.59 in the second cycle. From this the inquiry and assignment methods can improve student achievement and student tenacity.